Strategy Making Under Causal Ambiguity: Conceptual Issues and Empirical Evidence - Mosakowski, Elaine (Organization Science, 1997)
This paper examines how a decision maker's inability to discern the causal structure that leads to his firm's success or failure (i.e., causal ambiguity) shifts attention away from making the so-called “right” decision toward managing the strategy-making process. For this process, I advocate a calculative experimentation approach that lies somewhere between truly random trial-and-error behavior and planned solutions. To suggest this approach, this paper defines causal ambiguity and proposes a typology of causal ambiguities. The primary distinctions in this typology derive from the knowability of causal structures and inputs to the causal structures, and what is actually known by relevant actors. A simple model of decision making is presented based on a hypothesis-testing approach to problem solving, with tentative rules about the relationships between actions and outcomes being revised in a Bayesian fashion. This paper also considers the circumstances under which causal ambiguity will affect strategy making: in particular, pointing to the overall complexity both within the firm and in its environment. To illustrate the effect of causal ambiguity, I examine the prototypical strategic problem of finding the most profitable use of a firm's assets; my objective is to consider the choices and contingencies facing a decision maker operating under causal ambiguity. This paper presents a series of hypotheses that describe these choices and contingencies. In a sample of computer firms, a subset of these hypotheses are tested empirically in the context of experimental diversification as a specific case of calculative experimentation. The empirical results are generally supportive of the idea that diversification may occur as firms search to assign resources to uses. The paper concludes with a general discussion of the relationship between calculative experimentation versus purely random trial-and-error behavior and planned approaches to strategy making. The process of decision making may itself transform over time as causal understanding increases.